Europe and the Decline of Social Democracy in Britain - Williamson, Adrian (Boydell & Brewer, Incorporated, 2019)
This book explores the nation's gradual disenchantment with both social democracy and the EEC/EU, culminating in the 2016 vote for Brexit. It offers a much-needed historical perspective to the current political crisis in Britain.